Applied economics - Dinio, Rosemary P.; Villasis, George A. (Manila, Philippines Rex Book Store, 2021)
Applied Economics for senior high school students is distinct from other economics textbooks as it does not solely focus on the study of economic theories. What is more important is that it teaches the students to apply these theories to real-life situations. A fundamental subject in senior high school following the business track, the worktext serves as a groundwork for future business endeavors or entrepreneurial courses in college--Back cover.
Chapter 1: introduction to applied economics -- Chapter 2: Applications of demand and supply -- Chapter 3: Industry and environmental analysis: business opportunity identification -- Chapter 4: Socioeconomic impact study.
Includes bibliographical references and index.
Keywords: Economics -- Study and teaching (Secondary); Economics -- Textbooks; Economics -- Problems, exercises, etc